Tourism and Protected Areas: Benefits Beyond Boundaries The Vth IUCN World Parks Congress - Bushell, Robyn (CABI, 2014)
More than 3000 delegates gathered in Durban, South Africa for the Vth World Parks Congress,1 held every ten years by the World Commission for Protected Areas (WCPA), of the World Conservation Union (IUCN).2 The 11 years since the previous Congress witnessed accelerated global change and the rapid loss of priceless ecosystems due to deforestation, desertification, war and innumerable other natural and human forces (WCPA, 2003). The Congress theme Benefits Beyond Boundaries and the sessions highlighted many achievements and new directions since the 1992 Congress in Caracas, Venezuela. The most significant achievement for protected areas is the increase in total area to 18.8 million km2 across just over 100,000 sites. The area now under protection extends to 11.5% of the surface of the earth, doubling the protected estate since 1992 (Chape, 2003). Conversely, this achievement intensifies the critical issues facing protected areas, and in order to address these, new approaches and new partnerships are essential